Evaluation of the Quality of Life after Surgical Treatment of Chronic Pancreatitis - Hildebrand, Philipp; Duderstadt, Stefanie; Jungbluth, Thomas; Roblick, Uwe Johannes; Bruch, Hans-Peter; Czymek, Ralf (JOP. Journal of the Pancreas, 2011)
Objective Pain is the main symptom of chronic pancreatitis. However, in addition to an improvement in pain symptoms, an increase in the quality of life also influences therapeutic success. The present paper evaluates the influence of surgery on chronic pancreatitis, and the early and late postoperative quality of life. Patients From March 2000 until April 2005, 51 patients underwent surgical treatment for chronic pancreatitis at our institution. Intervention Thirty-nine (76.5%) patients were operated on according to the Frey procedure and, in 12 (23.5%) patients, a Whipple procedure was performed. Study design Patient data were documented throughout the duration of the hospital stay. Postoperative follow-up data were recorded retrospectively. Main outcome measures Postoperative follow-up with postoperative pain scores and quality of life were carried out using a standardized questionnaire. Results During a median follow-up period of 50 months, an improvement in pain scores was observed in 92.3% of the patients in the Frey group and in 66.7% in the Whipple group. The indices for global quality of life and for physical and emotional status increased in both surgical groups. Conclusion For patients with chronic pancreatitis, the decisive factor is the quality of life, particularly concerning pain and metabolic changes. The Frey procedure seems to offer advantages with respect to long-term freedom of pain and low risk of surgery-induced pancreatic insufficiency. Image: University of Schleswig-Holstein. Lübeck, Germany.